Genetics of Thyroid-Stimulating Hormone Receptor—Relevance for Autoimmune Thyroid Disease - Stefan, Mihaela; Faustino, Larissa C. (Frontiers in Endocrinology, 2017)
Production of thyroid-stimulating hormone receptor (TSHR) antibodies represent the hallmark of Graves’ disease (GD) pathogenesis. Thus, for more than two decades the TSHR gene has been at the center of studies intended to elucidate its contribution to disease pathology. The advent of genome-wide association technology allowed to establish a strong association of the TSHR gene with GD. Subsequent fine-mapping studies narrowed the disease-susceptibility region to a 40 Kb sequence in intron 1, where at least five GD-associated SNPs in tight linkage disequilibrium were identified. The current challenge is to understand the functional mechanisms by which these polymorphisms modify physiological processes and trigger disease. The aim of this review is to summarize the current knowledge on the role of the TSHR gene in GD pathogenesis which has been gained through linkage and association studies, as well as to discuss the emerging mechanisms underlying biological implications of TSHR variants in the development of GD.